Brain drain and the gulf in world labor market : an analysis of employment conditions of highly skilled Pakistanis in Finland’s ICT sector - Khan, Jawaria (2018)
Brain drain is a term referring to the phenomenon of international transfer of human capital resources. It means that the most skilled, talented and highly educated people of developing nations migrate to developed countries to achieve a higher standard of living. The source country is usually a poor country, which is unable to provide well-paid jobs and higher incomes according to the talent of the workers. This unequal development of the world forces the potential sources of economic growth (human capital) to migrate from developing countries to the developed countries. In the developed country, the human capital of the low-income countries has better-paid jobs relative to its home country. However, due to oversupply of labor from the developing countries, the employers of the developed economies get the room to discriminate them on the basis of wages. Therefore, this thesis interrogates if the employment conditions including slaries of highly skilled migrants are, compared to their equally qualified native counterparts, same or do these migrants from developing countries face any sort of labor market discrimination? The methodology adopted to probe the research questions has been a case study of the Pakistani students, who came to Finland to pursue their higher education and later became a part of the Finnish labor market. For a perfect qualitative research setting, only private companies’ employees in the ICT sector of Finland, having less than two years of experience have been interviewed. By taking a fresh approach to dependency theory of development, the research draws a linkage between labor exploitation in terms of wages and other employment conditions. Instead of discussing the financial capital dependence of periphery on the center, the thesis examines the macroeconomic dependence of human capital of the global South on the global North. The findings of the research indicate that although wage discrimination between native and migrant workers in Finnish ICT sector is not explicitly visible, yet there are certain barriers which question the social inequality for the migrant employees. Language proficiency, or lack thereof, plays a major role in the recruitment, selection, retention and promotion of migrant employees. Small companies try to exploit the unawareness of international employees by not paying them market competitive salaries. Also, the recognition of prior work experience from developing countries is not acknowledged and hence, not adjusted in the salaries. Considering this whole scenario of labor market discrimination, the research also establishes the fact that the migrant workers do not want to return to their home country because they still find themselves better off. Hence, the high skilled human capital of peripheral countries is economically dependent on the human capital of core countries.